Usefulness of à la carte antigens for bird fancier's lung serodiagnosis: total dropping extract and/or dropping's microflora antigens. Issue 10 (October 2017) - Rouzet, Adeline; Reboux, Gabriel; Dalphin, Jean‐Charles; De Vuyst, Paul; Laboissière, Audrey; Valot, Benoit; Millon, Laurence; Roussel, Sandrine
Abstract : Abstract : Bird fancier's lung (BFL) is a pulmonary disease caused by inhalation of avian proteins. The involvement of the microorganisms of droppings has been assumed in the past and this idea still persists today. Our study aimed to compare by immunoprecipitation assay the detection of antibodies against both droppings and microorganisms in the sera of patients ( n =15) and asymptomatic exposed controls ( n =18). We found that 14/15 BFL patients had negative serological results for isolated microorganisms of the droppings, only one positive against Enterobacter sakasakii . Serological arguments were in accordance with diagnosis in 87% of cases by testing à la carte antigens from each bird dropping versus 20% using the standard antigenic panel. Otherwise, the microorganisms antigens issued from dropping flora were negative in 93% of cases. Consequently, it's preferable to use the total extract from the patient's bird droppings to establish the serodiagnosis of the disease.